Psikoedukasi sebagai pelatihan perencanaan karir siswa kelas IX - Pravita, Dea Fitria; Amelasasih, Prianggi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
School period is a crucial stage in determining the direction of student’s careers, especially at the junior high school level. The majority of students at the junior high school level do not yet have a clear picture of their career plans. This study aims to help students understand career planning using a psychoeducational approach. This study is a quasi-experimental study with a one-group pre-posttest design. The participants in this study consisted of 20 ninth-grade students of Madrasah Tsanawiyah Masyhudiyah who were selected based on low pre-test scores. The research process consisted of three stages: pre-test, psychoeducation treatment, and post-test. The data analysis of this study used the Wilcoxon test. The results of this study indicate that career planning psychoeducation is effective in improving students' career planning abilities. Career planning psychoeducation can be used as a method that can be used by teachers to help students plan their careers and futures more maturely.